PENGOLAHAN AIR SUMUR GALI DENGAN METODE AERASI-FILTRASI MENGGUNAKAN AERATOR GELEMBUNG DAN SARINGAN PASIR CEPAT UNTUK MENURUNKAN KADAR BESI (Fe) DAN MANGAN (Mn) - La Aba; Bahrin Bahrin; Armid A (Universitas Halu Oleo, 2017)
A research on well water treatment has been done by aeration-filtration method using bubble aerator and quick sand filter to decrease iron (Fe) and manganese (Mn) concentration. The aim of this research is to know the decrease of Fe and Mn content in dug well water after processing using bubble aerator and fast sand filter with 15, 30 and 45 minute contact variations. Measurements of Fe and Mn concentrations were performed with the Ultraviolet-Visible (UV-Vis) spectrophotometric instrument. The initial concentration of Fe in well water before treatment was 3.8 mg / L and manganese (Mn) was 5.07 mg / L. After aeration of 15, 30 and 45 minutes, the Fe concentration decreased to 3.20; 1.38 and 1.23 mg / L with the effectiveness of each treatment of 15.78; 63.68 and 67.63%, while Mn concentration was found to be 3.3; 2,1 and 1,7 mg / L with effectiveness of processing 34,91; 58.57 and 66.46% respectively. Further aeration-filtration well treatment at contact time 15, 30 and 45 minutes yields a final Fe concentration of 0.89; 0.62 and 0.28 mg / L with the processing effectiveness of 76.57 each; 83.68 and 92.63%, and final concentration of Mn of 4.4; 3,1 and 1,5 mg / L with processing effectiveness 13,21; 38.85 and 70.41%. Thus, the results obtained through aeration-filtration treatment on Fe and Mn levels only resulted in an effective decrease in Fe (92.63%) after 45 minutes. Keywords: Dug well, Aerasi-filtration, Aerator bubble, Iron content (Fe), Manganese content (Mn)